Risk Factors Affecting The Incident Of Baby Blues Syndrome - Muh. Arief Wahyu Adama; Irma Santy; Irwan, Irwan (Sean Institute, 2024)
Twenty articles were reviewed using a synthesis table to see the variables that influence baby blues syndrome. Of the 20 articles, 10 articles mention age as an influential factor, with several advantages including data that represents both local and international data with the latest publications and samples that are suitable for analysis. These articles also identify the main variables that influence the incidence of baby blues syndrome, and emphasize the need for interventions to reduce the risk of this syndrome. However, there are several limitations, such as potential bias in terms of data sources, prioritization of data according to the researcher's hypothesis which can influence research results, and insufficient population coverage in some literature studies. Apart from the age factor, the author found seven articles that examined educational factors and five articles that discussed employment factors as variables that influence the incidence of baby blues syndrome. Differences in analysis results regarding the most common factors in the incidence of baby blues syndrome can be caused by different locations and sample populations. One of the strengths of these articles is their detailed and detailed discussions, arranged using certain procedures or stages, and presenting abstracts and conclusions that are easy to understand.